Strategies to Fight Stigma toward People with Mental Disorders: Perspectives from Different Stakeholders. (11th October 2012) - Corbière, Marc; Samson, Esther; Villotti, Patrizia; Pelletier, Jean-François
Abstract : This study aims to provide a more complete and exhaustive perspective on the whole range of potential strategies to fight stigma by considering the perspectives of different stakeholders. Delegates to a Canadian conference were invited to participate in a survey that focused on stigma, from which the responses to the following question were analyzed: tell us briefly what you do to reduce prejudice and stigma toward people with a diagnosis of mental disorder? From 253 participants, 15 categories of strategies to fight stigma were identified from the verbatim (e.g., sharing/encouraging disclosure). These categories fell under six main themes: education, contact, protestation, person centered, working on recovery and social inclusion, and reflexive consciousness. The occurrence of these themes was different among stakeholders (clinical, organizational, and experiential knowledge). For example, people with mental disorders (experiential knowledge) often mentioned contact and person centered strategies, while mental health professionals (clinical knowledge) preferred education and working on recovery and social inclusion strategies. The results from this study highlight the need to pay more attention to the concept of disclosure of mental disorders in the process for de-stigmatization. Future studies are needed to assess the impact of the emerging strategies to fight stigma in the community.